2015
DOI: 10.1371/journal.pone.0119978
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Naturally Existing Cavity Couplings in Proteins

Abstract: Couplings between protein sub-structures are a common property of protein dynamics. Some of these couplings are especially interesting since they relate to function and its regulation. In this article we have studied the case of cavity couplings because cavities can host functional sites, allosteric sites, and are the locus of interactions with the cell milieu. We have divided this problem into two parts. In the first part, we have explored the presence of cavity couplings in the natural dynamics of 75 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 98 publications
2
5
0
Order By: Relevance
“…Thus, the V67L mutation may rearrange active site geometry and dynamics to enhance intein activity through its effects on cavities. Couplings between cavities in proteins have indeed been demonstrated by MD . Consistent with these ideas, our previous work showed that L2 and N139 experience some of the largest chemical shift perturbations caused by V67L, away from the site of mutation .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, the V67L mutation may rearrange active site geometry and dynamics to enhance intein activity through its effects on cavities. Couplings between cavities in proteins have indeed been demonstrated by MD . Consistent with these ideas, our previous work showed that L2 and N139 experience some of the largest chemical shift perturbations caused by V67L, away from the site of mutation .…”
Section: Resultssupporting
confidence: 70%
“…Couplings between cavities in proteins have indeed been demonstrated by MD. 43 Consistent with these ideas, our previous work showed that L2 and N139 experience some of the largest chemical shift perturbations caused by V67L, away from the site of mutation. 14 An additional possibility is that the V67L mutation may affect the intein−extein junctions and intein-extein interaction, which may shift active site conformation and dynamics to favor catalysis.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
“…In addition, a useful descriptor should be also able to give information onand possibly, to predictthe interactions between the cavity and the interacting molecules. 27,28 Here, we present a new computational protocol that is able to quantitatively describe both the shape and electrostatic properties of a given subregion of a protein on a rigorous ground by means of a moment-based approach using the Zernike polynomials. 29−31 The main advantage of this method is its ability to describe subregions of a molecular surface in a compact way using a single vector of numbers to provide quantification of both the geometrical shape and the electrostatic potential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although more than 1000 allosteric sites are known [ 1 ] many more need to be characterized. In fact several pairs of allosteric endpoints may exist in a protein [ 2 ] which increases the number of candidate pairs that communicate. This problem becomes even more important when one considers the fact that most known cancers result from disruption of allosteric communication as a result of single mutations [ 3 , 4 ] and the number of proteins associated with this phenomenon is very large.…”
Section: Introductionmentioning
confidence: 99%